8 MARZO 2023 EMPRENDIMIENTO CARRERA DE MARKETING 2 PARTE - Aviles Quijano, Jaime Eduardo (2023)
MARCH 8, 2023 THE OPEN HOUSE OF ENTREPRENEURSHIP OF THE MARKETING CAREER WAS HELD PART 2 FACULTY OF ADMINISTRATIVE SCIENCES